Gold in our veins - Higgins, Mark Lewis Lim; Ayala Museum (Makati City : Ayala Foundation, 2019)
"This series of paintings are ultimately a celebration of my own hybrid lineage. Indeed, it is homage to all of our ancestries--particularly to ones so deeply rooted in our DNA and or which many Filipinos may have never been aware. Far beyond the limits and borders of what become countries or nations, we are all maps of our ancestors. This is my tribute to the gold that flows in all of our veins." -- Mark Lewis Lim Higgins
Message from the Director / Ma. Elizabeth "Mariles" L. Gustilo -- Message from the artist / Mark Lewis Lim Higgins -- Illumina tenebras : Mark Lewis Lim Higgins, illuminating the darkness / Ambeth R. Ocampo -- Everywhere is here : Southeast Asia as medial space / David A. Henkel -- Notes on the exhibition : after a visit to the Ayala Museum / Ditas R. Samson -- Plates -- Object catalogue from the Ayala Museum collection -- Artist glossary -- About the artist -- About Ayala Museum
Published in conjunction with the exhibition Gold in our Veins: Mark Lewis Lim Higgins, Ayala Museum, 20 February to 26 May, 2019
Oversized
English
Keywords: Higgins, Mark Lewis Lim -- Exhibitions; Ayala Museum -- Exhibitions; Art, Philippine -- Exhibitions; Ethnology -- Philippines -- Exhibitions; Art, Southeast Asian -- Exhibitions; Southeast Asia -- Antiquities; Philippines -- Civilization -- Exhibitions